LAPROSCOPY-A DIAGNOSTIC AND THERAPEUTIC TOOL IN MANAGEMENT OF ACUTE ABDOMEN - Kamal, Mustafa; Ahmed, Tauqir; Bhatti, Aftab H.; Bhatti, Amir Ahmed (Journal of Ayub Medical College Abbottabad, 1998)
The role of laparoscopy in the management of patients presenting to one surgical firm with an acute abdomen is discussed. 37 laparoscopies were performed over a 24 months’ period and it altered the diagnosis in 24.3% of cases and the management in 13.5%of cases. At laparoscopy the diagnosis of appendicitis was made in 17 patients (76.4% were attempted laparoscopic appendectomies), pelvic inflammatory disease in 5 patients, torted ftmbrical cyst in 2 patients and free pus in the right lower peritoneum as a result of a perforated appendix was seen in 4 patients. Normal laparoscopy was performed in 5 patients and 2 patients who presented with a perforated duodenal ulcer had the diagnosis confirmed at laparoscopy. 2 laparoscopie3ere performed on trauma patients, one stabbing and one blunt trauma to the right hypochondrium. It has been demonstrated that diagnostic laparoscopic is a useful adjunct to the general surgeon’s armamentarium. It is suggested that the skill of laparoscopy is passed on to junior trainee surgeons who can use this technique to help attain a diagnosis in patients presenting with an acute abdomen